Analisis Pengaruh Inflasi dan GDP Terhadap Harga Saham Perusahaan Sektor Perbankan di Indonesia - Hardjanti, Ana Rusliani; Nurfadillah, Mursidah; Jamal, Sri Wahyuni (CV. ITTC INDONESIA, 2025)
This study addresses the issue of whether inflation and Gross Domestic Product (GDP) influence the stock prices of banking sector companies in Indonesia. The purpose of this research is to analyze the effect of inflation and GDP, both partially and simultaneously, on the stock prices in this sector. The research uses secondary monthly data from the 2020–2024 period, obtained from the Central Bureau of Statistics (BPS) and the Indonesia Stock Exchange (IDX). The analytical method employed is multiple linear regression, supported by partial tests (t-test), simultaneous tests (F-test), and classical assumption tests to ensure the validity of the regression model. The findings indicate that inflation does not have a significant partial effect on banking stock prices, whereas GDP has a significant positive effect. However, when analyzed simultaneously, both inflation and GDP have a significant impact on stock price movements. These results align with the Arbitrage Pricing Theory (APT) and fundamental analysis theory, which suggest that stock prices are influenced by a combination of macroeconomic factors. This study suggests that investors, market participants, and policymakers should consider economic growth indicators as a primary reference in making investment decisions in the banking sector.